Evaluation Of Antimicrobial Activity Of Eclipta Alba Leaf Extract For Food Preservation - Rajandran, R. Kushha (2020)
Leptospirosis caused by Leptospira, a spirochete bacterium, is a zoonotic and highly contagious disease, especially in humans, worldwide. The disease occurs when humans are exposed to water or the environment polluted by pathogens known as Leptospira interrogans (L. interrogans), especially during floods. In Malaysia, the incidence of this disease is seen to increase during the flood season because the victims take food contaminated with L. interrogans or exposed to the tissues, blood or urine of animals that have been infected with Leptospira.